Improved Analgesic Effect of Paravertebral Blocks before and after Video-Assisted Thoracic Surgery: A Prospective, Double-Blinded, Randomized Controlled Trial - Lihua Chu; Xiaolin Zhang; Yaping Lu; Guohao Xie; Shengwen Song; Xiangming Fang; Baoli Cheng (Pain Research and Management)
Despite being less invasive, patients who underwent video-assisted thoracic surgery (VATS) suffered considerable postoperative pain. Paravertebral block (PVB) was proven to provide effective analgesia in patients with VATS; however, there is no difference in pain relief between preoperative PVB and postoperative PVB. This study was aimed to investigate the analgesic efficacy of combination of preoperative and postoperative PVB on the same patient undergoing VATS. In this prospective, double-blinded, randomized controlled trial, 44 patients undergoing VATS were enrolled, and they received patient-controlled intravenous analgesia (PCIA) with sufentanil plus preoperative PVB (Group A, n = 15) or postoperative PVB (Group B, n = 15), or combination of preoperative and postoperative PVB (Group C, n = 14). The primary outcome was sufentanil consumption and PCIA press times in the first 24 hours postoperatively. Also, data of postoperative use of PCIA and visual analogue scale (VAS) were collected. In the first 24 hours postoperatively, median sufentanil consumption in Group C was 0 (0–34.75) μg, which was much less than that in Group A (45.00 (33.00–47.00) μg, p=0.005) and Group B (36 (20.00–50.00) μg, p=0.023). Patients in Group C pressed less times of PCIA (0 (0–0) times) than patients in Group A (2 (1–6) times, p<0.001) and Group B (2 (1–3) times, p=0.009). Kaplan–Meier analysis showed patients with combination of preoperative and postoperative PVB had a higher PCIA-free rate than patients with either technique alone (p=0.003). The VAS among the three groups was comparable postoperatively. The combination of both preoperative and postoperative PVB provides better analgesic efficacy during the early postoperative period and may be an alternative option for pain control after VATS. This trial is registered with ChiCTR1800017102.